2011
DOI: 10.1007/s10637-011-9668-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic C-1 analogue of 7-deoxypancratistatin induces apoptosis in p53 positive and negative human colorectal cancer cells by targeting the mitochondria: enhancement of activity by tamoxifen

Abstract: The natural compound pancratistatin (PST), isolated from the Hymenocallis littoralis plant, specifically induces apoptosis in many cancer cell lines. Unlike many other chemotherapeutics, PST is not genotoxic and has minimal adverse effects on non-cancerous cells. However, its availability for preclinical and clinical work is limited due to its low availability in its natural source and difficulties in its chemical synthesis. Several synthetic analogues of 7-deoxypancratistatin with different modifications at C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…This conjugation results in the lipidated protein LC3-II that is recruited to autophagosomal membranes and can be used as another marker for autophagy detection. 22 To confirm the results of autophagy seen by MDC staining, immunocytochemical analysis was used to detect the conversion of LC3-I to LC3-II. BxPC-3 treated with DRE at 2.5 mg/mL had a similar effect on the conversion of LC3-I to LC3-II, compared to the tamoxifen-treated cells.…”
Section: Dre Induces Prodeath Autophagy In Human Pancreatic Cellsmentioning
confidence: 99%
“…This conjugation results in the lipidated protein LC3-II that is recruited to autophagosomal membranes and can be used as another marker for autophagy detection. 22 To confirm the results of autophagy seen by MDC staining, immunocytochemical analysis was used to detect the conversion of LC3-I to LC3-II. BxPC-3 treated with DRE at 2.5 mg/mL had a similar effect on the conversion of LC3-I to LC3-II, compared to the tamoxifen-treated cells.…”
Section: Dre Induces Prodeath Autophagy In Human Pancreatic Cellsmentioning
confidence: 99%
“…As observed in the Saos-2, BxPC-3 and PANC-1 cells above [23,26], the caspase inhibitor Z-VAD-FMK (at both 25 and 50 μM) could not protect HCT116 cells from the apoptotic onslaught of compound 2 (1 μM) [27]. This confirmed the action of this alkaloid to be at the stage of mitochondrial destabilization, upstream of executioner caspase activation, which in turn caused the release of various apoptogenic factors involved in both caspase dependent and independent pathways of apoptotic induction [27]. Similar effects were observed for alkaloid 2 in human neuroblastoma (SHSY-5Y) and breast adenocarcinoma (MCF-7) cells [28].…”
mentioning
confidence: 83%
“…To this extent, compound 2 was able to decrease MMP, increase levels of ROS and cytochrome c in isolated mitochondria and induce autophagic effects in both cell lines [27]. As observed in the Saos-2, BxPC-3 and PANC-1 cells above [23,26], the caspase inhibitor Z-VAD-FMK (at both 25 and 50 μM) could not protect HCT116 cells from the apoptotic onslaught of compound 2 (1 μM) [27]. This confirmed the action of this alkaloid to be at the stage of mitochondrial destabilization, upstream of executioner caspase activation, which in turn caused the release of various apoptogenic factors involved in both caspase dependent and independent pathways of apoptotic induction [27].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Although the precise mechanism of its affinity for cancerous mitochondria remains elusive to date, we have found that the natural compound pancratistatin (PST), isolated from the Hymenocallis littoralis plant, specifically induces apoptosis in numerous cancer cell types with minimal effect on noncancerous cells by mitochondrial targeting (16)(17)(18)(19)(20). We have previously synthesized JCTH-4, a C-1 acetoxymethyl analog of 7-deoxypancratistatin, and found it to possess comparable anticancer activity to ABBREVIATIONS: AIF, anti-apoptosis-inducing factor; AV, annexin V; BMX, basement membrane extract; DCF, 29,79-dicholorofluorescein; DIC, differential interference contrast; FBS, fetal bovine serum; H 2 DCFDA, 29,79-dicholorofluorescin diacetate; MMP, mitochondrial membrane potential; NAC, N-acetyl cysteine; PBMC, peripheral blood mononuclear cell; PBMCs V1/2, peripheral blood mononuclear cells from healthy volunteer 1/2; PI, propidium iodide; PL, piperlongumine; PST, pancratistatin; ROS, reactive oxygen species; RPMI, Roswell Park Memorial Institute; TBST, Tris-buffered saline-Tween 20; TMRM, tetramethylrhodamine methyl ester that of PST, inducing apoptosis in numerous cancer cell types by way of mitochondrial targeting (21)(22)(23)(24). Recently we created a C-7 hydroxylated version of JCTH-4, SVTH-6, a C-1 acetoxymethyl analog of PST, by de novo synthesis; to our knowledge, this is the first time that chemical synthesis of a PST analog with the full pharmacophore for anticancer activity has been achieved (24).…”
mentioning
confidence: 99%